Patterns of Bird-Ectoparasite Diversity and their Ecological Interaction from Different Habitats in Western Sarawak - Nurqamareena, Karim (Universiti Malaysia Sarawak (UNIMAS), 2020)
Birds are well distributed in a wide range of habitats in Sarawak. However, habitat modification and forest fragmentation may bring impact to the bird populations and distributions. Birds can serve as common hosts for ectoparasites such as ticks, mites, lice, fleas, and others (flies). Ectoparasites can affect both the survival and reproductive rates towards bird fitness. Some of the ectoparasites might act as the vectors for zoonotic diseases. Thus, it is essential to understand the diversity and distribution of birds in different habitats and their associated ectoparasites. This study was aimed to compare the species diversity of birds from three different habitats; mixed dipterocarp forest, mangrove forest, and rice field in Western Sarawak, Malaysia. Bird samplings were conducted between March 2017 and January 2018 which resulted in 472 individuals of birds from 70 species. The most dominant bird family recorded in this species is Pycnonotidae with eight species. A total of 119 individuals of birds were captured from rice fields, followed by mangrove forest (154 individuals) and mixed dipterocarp forest (119 individuals). Shannon diversity indices showed that the bird species from mixed dipterocarp forests was more diverse (H’= 3.199) when compared to mangrove forest (H’=3.089) and rice fields (H’=2.15). A total of ten feeding guilds were recorded from three different habitats in this study; (i) insectivores, (ii) omnivores, (iii) nectarivores, (iv) piscivores, (v) granivores, (vi) frugivores, (vii) carnivores, (viii) pischivores-insectivores, (ix) frugivores-granivores and (x) frugivores-nectarivores. A total of 205 individuals from 38 species of bird were found infested with ectoparasites. From these, 7,030 individuals of 59 ectoparasite species from three major groups (ticks, mites, and lice) were recovered from the birds caught. The ectoparasite species recovered include four species of ticks, 39 species of mites and 16 species of lice. This study shows that Nanopterodectes sp1 was the generalist ectoparasite species and most encountered with 2837 individuals and infested a total of 17 bird species with the lowest specificity index (d’=0.183). There was a total of 30 highly specific ectoparasite species (specialist) (d’=1.000) as they were only recovered from a single species of birds. Pied Fantail (Rhipidura javanica) was the only species that infested with all three major group (ticks, mites, lice) of ectoparasites. Pied Fantail also have the highest ectoparasite species diversity with H=2.082. Ectoparasite infestation prevalence was higher at rice field (60.80%) compared to mangrove forest (36.36%) and mixed dipterocarp forest (23.53%). The statistical analysis showed that there was significance difference in ectoparasite diversity recovered from birds in three different habitats. The most diverse ectoparasite species was recovered from mangrove forest (H=2.691) compared to mixed dipterocarp forest (H=2.282) and rice field (H=1.776). This study provides an information on the conservation of the birds in Sarawak by looking at the distribution and diversity of the birds and their ectoparasite.